1987
DOI: 10.1113/jphysiol.1987.sp016525
|View full text |Cite
|
Sign up to set email alerts
|

Development of ionic channels and cell‐surface antigens in the cleavage‐arrested one‐cell embryo of an ascidian.

Abstract: SUMMARY1. The developmental time course of the appearance of ionic channels was studied with the voltage-clamp technique at 8°C in ascidian embryos in which cleavage was arrested with cytochalasin B immediately after fertilization. The ontogeny of cell-surface antigens was also studied using monoclonal antibodies in both normal and cleavage-arrested embryos. The cleavage-arrested 1-cell embryo differentiates into a cell of epidermal type expressing Ca2+, anomalous rectifier and Ca2+-induced K+ channels, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 17 publications
5
35
1
Order By: Relevance
“…The inward-rectifier K+ channel was sometimes characteristic of epidermal differentiation in cleavage-arrested 1-cell embryos (Hirano & Takahashi, 1987). Also in the present experiment in some cases, currents through the inward-rectifier K+ channel continued to increase in epidermally differentiated a4-2 blastomeres (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The inward-rectifier K+ channel was sometimes characteristic of epidermal differentiation in cleavage-arrested 1-cell embryos (Hirano & Takahashi, 1987). Also in the present experiment in some cases, currents through the inward-rectifier K+ channel continued to increase in epidermally differentiated a4-2 blastomeres (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…extracellular materials are characteristic of epidermal differentiation in the ascidian (Hirano & Takahashi, 1987). In the neurally induced cells, large inward and outward currents appeared.…”
Section: Resultsmentioning
confidence: 99%
“…Later cleavage arrest yields cells that differentiate into neural or muscle types, which express different patterns of ion currents. The cleavage-arrested one-cell embryo is large enough that the time course of ionic current expression can be followed in real time as it differentiates from egg to epidermal cell (244). The egg Ca 2ϩ current disappears before gastrulation, and then a mature epidermal form reappears later.…”
Section: B Early Postfertilization Changes and Selective Channel Elimentioning
confidence: 99%
“…Part of the difficulty is due to the complexity of the multicellular interaction. If It has been shown that in the ascidian embryo cell cleavage is not necessary for differentiation of tissue-specific enzymes (4), antigens (5, 6), ultrastructural features (7), and various types of membrane excitability (5,8,9). Thus, when an embryo was cleavage-arrested at early stages and cultured, the large blastomeres further differentiated into neural, epidermal, muscular, or nonexcitable type, judging electrophysiologically from the type ofmembrane excitability (9).…”
Section: Introductionmentioning
confidence: 99%